2021
DOI: 10.3390/w13162296
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sustainable Biochars Produced from Kitchen Waste, Pig Manure, and Wood on Soil Erosion

Abstract: The influence of biochars on water retention, mitigating nutrient leaching, and pollutant removal in green infrastructure has been explored in the past. However, there is a lack of understanding on how feedstock (i.e., biomass) would affect biochar physicochemical properties and hence, overall erosion control (including infiltration, surface, and sub-surface runoff) in green infrastructure. The main purpose of this study was to investigate the effect of biochars produced from three different feedstocks (pig ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 87 publications
0
0
1
Order By: Relevance
“…This implies that the effect of biochar on erosion is not significant during the initial addition of 5% of biochar. This is inconsistent with the findings of Bordoloi et al (2019) [52] and Huang et al (2021) [72], who found a substantial influence of biochar on water retention capacity at an amendment ratio of 5%. The findings also suggest that biochar content of 5% may not be the optimal content for reduction of erosion rate.…”
Section: Influence Of Bas On Total Erosion Rate and Total Water Flow Ratecontrasting
confidence: 96%
“…This implies that the effect of biochar on erosion is not significant during the initial addition of 5% of biochar. This is inconsistent with the findings of Bordoloi et al (2019) [52] and Huang et al (2021) [72], who found a substantial influence of biochar on water retention capacity at an amendment ratio of 5%. The findings also suggest that biochar content of 5% may not be the optimal content for reduction of erosion rate.…”
Section: Influence Of Bas On Total Erosion Rate and Total Water Flow Ratecontrasting
confidence: 96%